Effect of Whey Kefir’s Goat Milk to Adhesion of Candida albicans to Resin Acrylic In Vitro - Faridiaz, Dedi; Azhari, Fariz (Faculty of Animal Science Universitas Brawijaya, 2025)
Candida albicans is a fungal who causes candidiasis in the oral cavity which one of the trigger is by using removable partial denture or full denture. It occurs due to Candida albicans adhesion on acrylic resin that initiates the process of invasion to oral mucosa adjacent. One method of prevention is by blocking the adhesion process of candida so that, the process of invasion does not occur. Whey kefir’s goat milk contain such as peptide, lactoferrin, organic acids, and enzymes protease has antimicrobial activity. The mechanism of antimicrobial whey kefir’s goat milk is by decreased hydrophobicity of Candida albicans. This study aims to prove that whey kefir’s goat milk has antimicrobial effects to the adhesion of Candida albicans on acrylic resin in vitro. Experiments carried out by the method of inducing acrylic resin contain Candida albicans with some concentration of whey kefir’s goat milk. The treatment group concentration used were 5%, 10%, 15%, 20%, and 25% and the negative control groups are 0%. Data were analyzed using normality and homogeneity tests, which confirmed non-parametric conditions. Therefore, Kruskal–Wallis and Mann–Whitney tests were used and showed significant differences among treatment groups (p < 0.05). Spearman’s correlation revealed a strong negative relationship between whey kefir concentration and Candida albicans adhesion (R = –0.957; p < 0.05).The conclusion of this research is whey kefir’s goat milk has the effect of inhibiting the adhesion of Candida albicans on acrylic resin.